Mass cytometric analysis of circulating immune landscape in primary central nervous system lymphoma - Wu, Yuchen; Lv, Liwei; Liu, Jing; Sun, Xuefei; Gao, Chunji; Sun, Shengjun; Ji, Nan; Wang, Wenjing; Liu, Yuanbo (Frontiers in Immunology, 2025)
IntroductionThe peripheral immune profiles of patients with primary central nervous system lymphoma (PCNSL) remain poorly characterized. Investigating immune dysregulation in PCNSL may help elucidate the underlying disease mechanisms.MethodsWe aimed to define the circulating immune landscape in PCNSL by characterizing the immune cell profiles in 16 patients and 6 healthy participants using mass cytometry.ResultsPatients exhibited significant alterations in peripheral blood mononuclear cells, including expansion of CD45RO+ classical monocytes (p=0.017), reduced intermediate subsets (p=0.01), and elevated CD38 expression (p<0.001). The number of terminally differentiated CD8+CD57+ T cells increased (p=0.013), and treatment induced effector T cell (CD8+ T effector/effector memory cells, p<0.05) expansion, accompanied by co-upregulation of CD38, HLA-DR, and CD107a (p<0.01). Patients < 60 years had higher frequencies of CD8+ naïve T cells (p<0.05), and progressive disease correlated with CD56brightNK cell accumulation (p<0.01).Conclusionthe circulating immune landscape in PCNSL is characterized by skewed monocyte activation, T cell terminal exhaustion, and chemotherapy-induced effector T cell expansion. Our findings link peripheral immune features to the tumor microenvironment biology. Understanding these systemic immune alterations may provide insights into tumor immune evasion and offer a roadmap for reversing PCNSL-associated immunosuppression.